Minerals Crime: Crimes in the Supply Chains of Critical Energy Transition Minerals - United Nations Office on Drugs; Crime (United Nations, 2025)
This research publication focuses on the unlicensed, unregulated, or otherwise illegal extraction, transport and trade of minerals that are critical for the energy transition which may constitute crimes in their supply chains. For the purpose of this study, these minerals are defined in accordance with the United Nations Secretary-General’s Panel on Critical Energy Transition Minerals, which identifies them as critical energy transition minerals (CETMs). These include, but are not limited to, bauxite (aluminium), cobalt, coltan (tantalum), copper, graphite, lithium, manganese, nickel and rare earth elements (REEs). The study highlights the importance of including minerals crime as a key component of broader discussions on responsible mineral sourcing and the environmental impact associated with the mining sector. As regulatory frameworks become increasingly complex and focused on innovation, adaptation and mitigation, new opportunities arise for transnational organized crime and corruption to exploit regulatory gaps, evade controls and distort mineral supply chains.